PROGRAM PENANGGULANGAN KEMISKINAN MELALUI KELOMPOK USAHA BERSAMA (KUBE) - Abd. Kadir, Iriyani; Kamis, Yusuf (EDUTECH CONSULTANT, 2018)
This research was conducted in Tidore Islands City and was the focus of the target in Tidore District. The method in this study is qualitative descriptive. The stages of the study included primary data sources which were informants, namely the Head of Social Services, Manpower and Transmigration, Head of District, Head of Village, and KUBE Management, as well as supporting data in the form of written documents and technical guidelines from the Tidore City Social Service and Transmigration Office Island. Data collection techniques through observation (observation) and interviews (interviews), usinginstruments tape recorder, questionnaires and notebooks. Data analysis was carried out by flowing stages of data reduction, data presentation, conclusion and verification. As for testing the credibility of data through increasing persistence to be able to provide accurate and systematic data descriptions of what was recorded, discussion of colleagues can make data more accurate through Focus Group Discussion (FGD), checking members by discussing research results to data sources that have been provide data, and check data with experts, namely: Expert Staff in the implementation of Regional Government focused on policy.